Interface effect enhanced liquid crystal polyester, high-thermal-conductivity liquid crystal polyester composite material and preparation method and application of high-thermal-conductivity liquid crystal polyester composite material
By preparing interface effect-enhanced liquid crystal polyester in liquid crystal polyester and hot pressing with graphene nanosheets, the problem of insufficient dispersion and interface compatibility of graphene in liquid crystal polyester is solved, which significantly improves the Thermal conductivity achieves efficient thermal management.
Patent Information
- Application Number
- CN202411289541.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-14
AI Technical Summary
In the prior art, graphene has insufficient dispersion and interfacial compatibility in liquid crystal polyester, resulting in limited improvement in thermal conductivity, and commonly used modification methods have problems such as poor solvent dispersion ability, large toxic side effects, and complex methods.
By performing catalytic polycondensation reaction of biphenyl dihexanol and perylene-3,9-dicarboxylic acid, an interface effect-enhanced liquid crystal polyester was prepared, and the graphene nanosheets were stirred in an organic solvent, and then dispersed ultrasonically and then subjected to hot pressing. The treatment is made to form a highly thermally conductive liquid crystal polyester composite material.
It significantly improves the interface compatibility between graphene and liquid crystal polyester, reduces the interface thermal resistance, and improves the thermal conductivity of the composite material. The vertical surface thermal conductivity coefficient reaches 0.848 W m-1K-1, and the process is simple and easy to form.
Smart Images

Figure CN119264401A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of thermal conductive composite materials, and specifically relates to an interface effect enhanced liquid crystal polyester, a high thermal conductive liquid crystal polyester composite material, and a preparation method and application thereof. Background Art
[0002] With the miniaturization of devices and the increasing density, thermal management has become one of the core challenges facing modern electronic products. Especially for flexible electronic products, the demand for efficient heat dissipation has led to the rapid development of research on thermally conductive polymers. Liquid crystal polymers, due to their unique oriented arrangement structure, can effectively reduce phonon scattering, thereby significantly improving the thermal conductivity of polymers. At present, research on intrinsically thermally conductive thermoplastics mainly focuses on enhancing the intermolecular interactions between polymer chains. Carbon-based materials are widely used in the preparation of thermally conductive composite materials due to their excellent thermal conductivity, light weight and excellent processing and forming properties. In particular, graphene, due to its excellent thermal conductivity and light weight, meets the requirements of modern electronic devices for thin and short heat dissipation solutions. However, the compatibility problem of the composite interface significantly limits the further improvement of thermal conductivity. At present, the literature reports often use dispersants, surface oxidation modification, graft modification and multiple fillers to improve the dispersion and interfacial action of graphene in epoxy resin, such as CN115772328B uses multiple fillers such as polydopamine and liquid metal to improve the dispersibility of graphene in cyanate, CN118471402A carries out hydroxyl grafting on the graphene surface, and CN118496538A uses strong oxidants such as nitric acid to oxidize graphite to obtain partial oxidation of graphene, which promotes its interaction with polyimide. The above methods have the problems of poor solvent dispersibility, large toxic and side effects of dispersants, poor interfacial interaction between graphene and polymer after dispersion, and complex methods. Therefore, it is necessary to develop a graphene / liquid crystal polyester composite material that can enhance the interfacial interaction force of graphene in liquid crystal polyester and improve thermal conductivity. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art. The primary purpose of the present invention is to provide a liquid crystal polyester with enhanced interface effect.
[0004] Another object of the present invention is to provide a method for preparing the interface effect enhanced liquid crystal polyester.
[0005] Another object of the present invention is to provide a method for preparing a high thermal conductivity liquid crystal polyester composite material.
[0006] Another object of the present invention is to provide a high thermal conductivity liquid crystal polyester composite material.
[0007] Another object of the present invention is to provide an application of the composite material containing the interface effect enhanced liquid crystal polyester and the high thermal conductivity liquid crystal polyester.
[0008] The purpose of the present invention is achieved through the following technical solutions: An interfacial effect enhanced liquid crystal polyester, the structural formula of which is shown in Formula I: Formula I.
[0009] Preferably, the number average molecular weight (Mn) of the interface effect enhanced liquid crystal polyester is in the range of 7500 g / mol to 70000 g / mol, particularly in the range of 10000 g / mol to 50000 g / mol, more preferably in the range of 15000 g / mol to 35000 g / mol.
[0010] The method for preparing the above-mentioned interface effect enhanced liquid crystal polyester comprises the following steps: Biphenyl dihexanol and perylene-3,9-dicarboxylic acid are mixed, a catalyst is added, and heated for polycondensation reaction, and then the heating reaction is continued while filtering to obtain an interface effect enhanced liquid crystal polyester.
[0011] Preferably, the molar ratio of biphenyl dihydric alcohol to perylene-3,9-dicarboxylic acid is 1-2:1-2, more preferably 1:1.
[0012] Preferably, the heating polycondensation reaction is carried out at 150-180°C for 2-4 hours, more preferably at 170°C for 3 hours; The conditions for the continued heating reaction are 150-180° C. for 2-4 hours, preferably 170° C. for 3 hours; The polycondensation reaction is carried out under a protective atmosphere, which is a nitrogen atmosphere.
[0013] Preferably, the catalyst is anhydrous zinc acetate and antimony trioxide; The mass of the anhydrous zinc acetate is 0.1-0.3% of the total mass of the reaction system, more preferably 0.2%. The total mass of the reaction system is the sum of the masses of diphenyl diol, diphenyl diol, anhydrous zinc acetate and antimony trioxide.
[0014] The mass of the antimony trioxide is 0.2-0.4% of the total mass of the reaction system, and more preferably 0.3%.
[0015] The condition of the filtration is that the vacuum degree is lower than 30Pa.
[0016] A method for preparing a high thermal conductivity liquid crystal polyester composite material comprises the following steps: The graphene nanosheets and the interface effect enhanced liquid crystal polyester are dissolved in an organic solvent, stirred, ultrasonically dispersed, dried, and then hot-pressed to obtain a high thermal conductivity liquid crystal polyester composite material; The interface effect enhanced liquid crystal polyester is used as a matrix material, the graphene nanosheets are used as fillers, and the amount of liquid crystal polyester added accounts for 70% to 90% of the weight of the composite material.
[0017] Preferably, the CAS number of the graphene nanosheet is 7782-42-5.
[0018] The organic solvent is one of tetrahydrofuran, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylacetamide; The stirring time is 4 to 6 hours, more preferably 5 hours; The ultrasonic dispersion time is 4 to 6 hours, more preferably 5 hours; The hot pressing conditions are 150-200° C. for 10-15 min, more preferably 150° C. for 12 min.
[0019] Application of the above-mentioned composite material containing interface effect enhanced liquid crystal polyester and high thermal conductivity liquid crystal polyester in the preparation of electronic devices.
[0020] The above-mentioned composite material containing interface effect enhanced liquid crystal polyester and high thermal conductivity liquid crystal polyester is used as a heat dissipation material for electronic devices.
[0021] The present invention has the following advantages and beneficial effects compared to the prior art: (1) The thermal conductivity of the interface effect enhanced liquid crystal polyester prepared by the present invention in the vertical direction is 0.428 Wm -1 K -1 .
[0022] (2) In the thermally conductive composite material prepared by the present invention, a π-π stacking effect is formed between the synthesized liquid crystal polyester and graphene, which significantly enhances the compatibility of graphene and polyester and effectively reduces the interfacial thermal resistance between polyester and graphene, thereby further significantly improving the thermal conductivity of the composite material.
[0023] (3) The thermally conductive composite material prepared by the present invention has a thermoplastic polymer matrix, which is easy to shape and has a simple preparation process. After hot pressing, the matrix and the filler are more closely attached, resulting in a significant improvement in the thermal conductivity of the liquid crystal polyester composite material, and the vertical thermal conductivity coefficient can reach 0.848 W m -1 K -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1This is the infrared spectrum of the polymer synthesized in Example 1. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0026] If no specific experimental conditions are specified in the following embodiments, conventional experimental conditions or experimental conditions recommended by the reagent company are generally followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.
[0027] Biphenyl dihydric alcohol was prepared according to the method disclosed in CN 116496481 A.
[0028] Thermal conductivity system test: According to the thermal conductivity system test standard in GB / T 10297-2015, the performance of graphene nanosheet / liquid crystal polyester composites was evaluated using a thermal conductivity system tester. At least 3 parallel samples were tested in each group, and the results were averaged.
[0029] Example 1 This embodiment provides a method for preparing an interfacial effect enhanced liquid crystal polyester as follows: 3.54g of biphenyl dihexanol and 3.4g of perylene-3,9-dicarboxylic acid were subjected to polycondensation, 0.014g of anhydrous zinc acetate and 0.021g of antimony trioxide were added, and the reaction was carried out at 170 degrees Celsius for 3 hours under nitrogen protection. After slowly heating to 180 degrees Celsius, the vacuum degree of the system was reduced (below 30Pa) by vacuum filtration, and water and small molecules in the system were removed at the same time, so that the polycondensation reaction proceeded in the forward direction. After continuing to react at 170 degrees Celsius for 3 hours, the reaction was stopped, and the product was taken out to obtain an interface effect enhanced liquid crystal polyester, whose structural formula is shown in Formula I: Formula I.
[0030] The prepared interface effect enhanced liquid crystal polyester was subjected to infrared characterization test, and the infrared results are as follows: Figure 1 As shown. Among them, 1736cm -1 The stretching vibration absorption peak of the ester group C=O is 1010 cm -1 The C―O―C stretching vibration absorption peak is at the center, indicating the successful synthesis of the interface effect enhanced liquid crystal polyester. The thermal conductivity was tested and the experimental data showed that the thermal conductivity in the vertical direction was 0.428 W m -1 K -1 .
[0031] Example 2 This embodiment provides a high thermal conductivity liquid crystal polyester composite material, and the preparation method is as follows: 0.2 g of graphene nanosheets (Shenzhen Suiheng Technology Co., Ltd., CAS No.: 7782-42-5, thermal conductivity: 4937.8 W m -1 K -1 ) and 0.8 g of the interface effect enhanced liquid crystal polyester prepared in Example 1 were dissolved in 20 g of tetrahydrofuran, stirred (200 rpm) for 5 hours, ultrasonically dispersed (480 W) for 5 hours, and then the solvent was dried at 60 degrees Celsius and hot-pressed at 150 degrees Celsius for 12 minutes to obtain a high thermal conductivity liquid crystal polyester composite material, recorded as graphene nanosheets / liquid crystal polyester composite material.
[0032] The thermal conductivity of the prepared high thermal conductivity liquid crystal polyester composite material was characterized and tested. The experimental data showed that its thermal conductivity in the vertical direction can reach 0.848 W m -1 K -1 .
[0033] Example 3 This embodiment provides a high thermal conductivity liquid crystal polyester composite material, and the preparation method is as follows: 0.1 g of graphene nanosheets and 0.9 g of the interface effect enhanced liquid crystal polyester prepared in Example 1 were dissolved in 20 g of tetrahydrofuran, stirred (200 rpm) for 5 hours, ultrasonically dispersed (480 W) for 5 hours, and then the solvent was dried and hot-pressed at 150 degrees Celsius for 12 minutes to obtain a high thermal conductivity liquid crystal polyester composite material, which was recorded as graphene nanosheets / liquid crystal polyester composite material.
[0034] The thermal conductivity of the prepared high thermal conductivity liquid crystal polyester composite material was characterized and tested. The experimental data showed that its vertical thermal conductivity could reach 0.543 W m -1 K -1 .
[0035] Example 4 This embodiment provides a high thermal conductivity liquid crystal polyester composite material, and the preparation method is as follows: 0.3 g of graphene nanosheets and 0.7 g of the interface effect enhanced liquid crystal polyester prepared in Example 1 were dissolved in 20 g of tetrahydrofuran, stirred for 5 hours, ultrasonically dispersed for 5 hours, and then the solvent was dried and hot-pressed at 150 degrees Celsius for 12 minutes to obtain a high thermal conductivity liquid crystal polyester composite material, recorded as graphene nanosheets / liquid crystal polyester composite material.
[0036] The thermal conductivity of the prepared high thermal conductivity liquid crystal polyester composite material was characterized and tested. The experimental data showed that its thermal conductivity in the vertical direction was 0.483 W m -1 K -1 .
[0037] Comparative Example 1 A liquid crystal polyester was prepared with reference to the method disclosed in 202310356985.0, and the obtained product was shown in Formula II.
[0038] Formula II 0.2 g of graphene nanosheets and 0.8 g of liquid crystal polyester represented by formula II were dissolved in 20 g of tetrahydrofuran, stirred for 5 hours, ultrasonically dispersed for 5 hours, and then the solvent was dried and hot-pressed at 150 degrees Celsius for 12 minutes to obtain a liquid crystal polyester composite material.
[0039] The thermal conductivity of the prepared liquid crystal polyester composite material was tested. The experimental data showed that its thermal conductivity in the vertical direction was 0.433 W m -1 K -1 .
[0040] Comparative Example 2 0.2 g of graphene nanosheets and 0.8 g of epoxy resin were ultrasonically treated for 2 h, with an ultrasonic power of 700 W, an ultrasonic time of 5 min, and an interval of 5 min; then 0.045 g of dicyandiamide curing agent was added, and the mixture was cured at 120 ° C for 4 hours, 190 ° C for 4 hours, and 220 ° C for 2 hours to obtain a graphene / epoxy resin composite material.
[0041] The thermal conductivity of the prepared liquid crystal polyester composite material was tested. The experimental data showed that its thermal conductivity in the vertical direction was 0.133 W m -1 K -1 .
[0042] By comparing the thermal conductivity of Examples 2 to 4, we found that the composite material with 20% mass fraction of graphene has the best thermal conductivity. By comparing Example 2 with Comparative Examples 1 to 2, we found that the newly prepared interface effect enhanced liquid crystal polyester can effectively improve its interface compatibility with graphene and significantly improve the thermal conductivity of the composite material.
[0043] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An interfacial effect enhanced liquid crystal polyester, characterized in that: The structural formula is shown in Formula I: Formula I.
2. The interfacial effect enhanced liquid crystal polyester according to claim 1, characterized in that: The number average molecular weight Mn of the interface effect enhanced liquid crystal polyester is in the range of 7500 g / mol to 70000 g / mol.
3. The method for preparing the interface effect enhanced liquid crystal polyester according to claim 1 or 2, characterized in that: The steps include: Biphenyl dihexanol and perylene-3,9-dicarboxylic acid are mixed, a catalyst is added, and heated for polycondensation reaction, and then the heating reaction is continued while filtering to obtain an interface effect enhanced liquid crystal polyester.
4. The method for preparing the interfacial effect enhanced liquid crystal polyester according to claim 3, characterized in that: The molar ratio of biphenyl dihydric alcohol to perylene-3,9-dicarboxylic acid is 1-2:1-2.
5. The method for preparing the interfacial effect enhanced liquid crystal polyester according to claim 3, characterized in that: The conditions for the heating polycondensation reaction are to react at 150-180° C. for 2-4 hours; the conditions for the continued heating reaction are to react at 150-180° C. for 2-4 hours; The heating polycondensation reaction is carried out under a protective atmosphere.
6. The method for preparing the interface effect enhanced liquid crystal polyester according to claim 3, characterized in that: The catalyst is anhydrous zinc acetate and antimony trioxide; The mass of the anhydrous zinc acetate is 0.1-0.3% of the total mass of the reaction system; the mass of the antimony trioxide is 0.2-0.4% of the total mass of the reaction system.
7. A method for preparing a high thermal conductivity liquid crystal polyester composite material, characterized in that: The steps include: The graphene nanosheets and the interface effect enhanced liquid crystal polyester according to claim 1 or 2 are dissolved in an organic solvent, stirred, ultrasonically dispersed, dried, and then hot-pressed to obtain a high thermal conductivity liquid crystal polyester composite material; The interface effect enhanced liquid crystal polyester is used as a matrix material, and the graphene nanosheets are used as fillers; The amount of liquid crystal polyester added accounts for 70% to 90% of the composite material mass.
8. The method for preparing a high thermal conductivity liquid crystal polyester composite material according to claim 7, characterized in that: The organic solvent is one of tetrahydrofuran, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylacetamide; The stirring time is 4 to 6 hours; The ultrasonic dispersion time is 4-6 hours; the hot pressing condition is hot pressing at 150-200° C. for 10-15 minutes.
9. A high thermal conductivity liquid crystal polyester composite material, prepared according to the preparation method according to any one of claims 7 to 8.
10. Use of the interface effect enhanced liquid crystal polyester according to claim 1 or 2 and / or the high thermal conductivity liquid crystal polyester composite material according to claim 9 in the preparation of electronic devices.
Citation Information
Patent Citations
High-thermal-conductivity liquid crystal polyester composite material as well as preparation method and application thereof
CN116496481A
FFC (Flexible Flat Cable) containing heat-resistant and corrosion-resistant PET (Polyethylene Terephthalate) material and production process thereof
CN116970265A
Process for preparing linear polyesters
GB1042476A
Copolymerized polyester
JP1986095021A
Polyester polymer, method for producing the same and molded article
JP2009191110A